The Behavior of Electrostatic Droplets After Impacting Pepper Leaves - Kaiyuan Wang; Xiaoya Dong; Song Wang; Liang Dong; Zhouming Gao; Tao Wang; Xiaolong Wang; Xin Lu; Baijing Qiu (Horticulturae)
Electrostatic droplets can enhance deposition on target leaves. To comprehensively investigate the main factors affecting droplet adhesion and splashing after electrostatic droplet impact on pepper leaves, a specialized experimental platform was developed to capture the impact behavior of charged droplets on pepper leaves. The following four variables were examined: the applied voltage of the electrode ring, droplet size, impact velocity, and the relative distance from the impact point to the leaf tip (expressed as a percentage of the total leaf length). The results showed that all four factors had significant effects on droplet adhesion. The effect sizes (partial η2) of the four factors, in descending order, were impact velocity (0.935), applied voltage (0.907), impact position (0.895), and droplet size (0.505). Compared with non-electrostatic droplets, the increase in the maximum spreading factor of charged droplets was positively correlated with droplet size, impact velocity, and applied voltage but showed no significant correlation with the relative distance to the leaf tip. The critical velocity for splashing of electrostatic droplets decreased to a certain extent but increased with higher applied voltages. The influence of the four factors on droplet splashing decreases in the following order: impact velocity (odds ratio ≫ 1), charging voltage (odds ratio = 1.246), droplet size (odds ratio = 1.023), and impact position (odds ratio < 1). Among these, impact velocity has the most significant effect on splashing behavior. This study reveals the adhesion and splashing mechanisms of electrostatic droplets on flexible pepper leaves, providing theoretical support for the design of electrostatic spraying systems and the selection of operational parameters. The findings offer a scientific basis for optimizing droplet deposition, minimizing splash losses, and improving application efficiency in precision spraying.